ENHANCING SOCIAL EQUALITY THROUGH INCLUSIVE GREEN ECONOMIC POLICIES: A HOLISTIC MODEL FOR BALANCED DEVELOPMENT AND COMMUNITY EMPOWERMENT - Ratna; Khairil Anwar; Aiyub Yahya; Maisyura (PT. Radja Intercontinental Publishing, 2023)
This research aims to develop a policy model integrating community empowerment and green economic development to achieve social equity and environmental sustainability. Through an in-depth literature review, the study identifies key components of the policy model, factors influencing successful implementation, and innovative governance mechanisms. The proposed model consists of four main components: community asset mapping, capacity building, community-based green economy initiatives, and participatory monitoring systems. Key success factors include local leadership, resource access, supportive policies, multi-stakeholder partnerships, and community awareness. Proposed innovative governance mechanisms include community green economy councils, benefit-sharing systems, and participatory digital platforms. This research contributes theoretically by integrating concepts of community empowerment and green economy, while offering practical guidance for policymakers. Although limited to literature analysis, the findings provide a comprehensive framework for implementing community-centered and environmentally friendly sustainable development policies.